A Model for Developing a Value Attitude Toward Motherhood among Students - Tkachenko, I.V.; Evdokimova, E.V.; Komarova, K.Y.; Lisitskaya, L.G. (Èksperimentalʹnaâ psihologiâ, 2021)
The work is aimed at studying the psychological conditions of formation at the subjective level in adolescence of an emotionally positive accepting attitude toward the role of mother. The authors conducted a theoretical and empirical study aimed at exploring the relationship between the perceptions of the phenomenon of motherhood, adolescents’ relationships with their parents, and their attitudes toward their personality. Respondents aged 13-16 years of boarding school №1 “Cossack” of Armavir took part in the study. For the empirical study methods were used: “Perceptions of the ideal parent” (R.V. Ovcharova); PARI technique — “Parent-Child Relations” (E.S. Schaefer, R.K. Bell); Test-questionnaire of self-relation (V.V. Stolin, S.R. Panteleev). The results of the study allow us to state that there is a significant inverse relationship between the excessive emotional distance between parents and their child and the cognitive indicator of ideas about motherhood in boarding school students (-0.248). A similar relationship exists between parents’ excessive emotional distance from their child and their self-acceptance (-0.306), that is, the higher the distance, the lower the adolescent’s self-acceptance. It was proved that the child’s self-acceptance and his or her ideas about an ideal mother are interdependent factors (0, 281). Theoretical analysis of psychological research confirmed that the acceptance of motherhood as a special value is in close connection with the awareness of the meaning of one’s life and varies in its defined value depending on the internal position, experience of intrafamily relationships, internalized benchmarks and ideals. The results of the study formed the basis of the model of formation of the value attitude towards motherhood among students. Работа направлена на изучение психологических условий становления на субъективном уровне в подростково-юношеском возрасте эмоционально-позитивного принимающего отношения к роли матери. Авторами было проведено теоретико-эмпирическое исследование, направленное на изучение взаимосвязи между представлениями о феномене материнства, взаимоотношениями подростков с родителями и их отношением к своей личности. В исследовании приняли участие респонденты в возрасте 13—16 лет школы-интерната № 1 «Казачья» г. Армавира. Для эмпирического изучения использовались методики: «Представления об идеальном родителе» (Р.В. Овчарова); методика PARI — «Родительско-детские отношения» (Е.С. Шефер, Р.К. Белл); Тест-опросник самоотношения (В.В. Столин, С.Р. Пантелеев). Результаты исследования позволяют констатировать, что существует значимая обратная зависимость между излишней эмоциональной дистанцией родителей с ребенком и когнитивным показателем представлений о материнстве у учащихся школы- интерната (-0,248). Аналогичная связь существует между излишней эмоциональной дистанцией родителей с ребенком и его самопринятием (-0,306), т. е. чем выше дистанция, тем ниже уровень самопринятия подростка. Доказано, что самопринятие ребенка и его представления об идеальной маме являются взаимозависимыми факторами (0,281). Теоретический анализ психологических исследований подтвердил, что принятие материнства как особой ценности находится в тесной связи с осознанием смысла своей жизни и системой ценностей, сформированной в зависимости от внутренней позиции, опыта внутрисемейных отношений, усвоенных эталонов и идеалов. Полученные результаты исследования легли в основу модели формирования ценностного отношения к материнству у учащейся молодежи.